1996
DOI: 10.1074/jbc.271.51.32810
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of SUG2

Abstract: Using a genetic strategy designed to find proteins involved in the function of the Saccharomyces cerevisiae transcriptional activator GAL4, we isolated mutants in two genes which rescue a class of gal4 activation domain mutants. One of these genes, SUG1, encodes a member of a large family of putative ATPases, the Conserved ATPase containing Domain (CAD) proteins (also known as AAA proteins) that are involved in a wide variety of cellular functions. Subsequently, SUG1 was identified as a subunit of the 26 S pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…The gal4D protein does not activate the GAL genes sufficiently to allow growth on galactose as the sole carbon source (1). Recessive mutations in SUG1 and SUG2 have been identified that partially restore the ability of gal4D to activate transcription (1)(2)(3). In strains carrying the sug1-1 or sug2-1 alleles, reporter gene activity was restored to ϳ55% and 70%, respectively (1,4).…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…The gal4D protein does not activate the GAL genes sufficiently to allow growth on galactose as the sole carbon source (1). Recessive mutations in SUG1 and SUG2 have been identified that partially restore the ability of gal4D to activate transcription (1)(2)(3). In strains carrying the sug1-1 or sug2-1 alleles, reporter gene activity was restored to ϳ55% and 70%, respectively (1,4).…”
mentioning
confidence: 94%
“…These fragments were purified and transformed into Sc530 (SUG2::URA3 pMTL-SUG2), which is congenic to W303 (3,18). The transformants were plated to glucose medium.…”
Section: Identification Of the Sug2 Mutation In The Crl13 Strain-jamesmentioning
confidence: 99%
See 3 more Smart Citations